The Development of Plant Regeneration System from Callus of Pineapple (Ananas comosus L.) - De Silva, Angela Ee (2005)

(untitled)
Malaysia’s production of canned pineapples has been decreasing since 1992. Two important factors that have been a hindrance to the progress of this industry are competition from other producers and the increasing demand for fresh pineapples. Current varieties need to undergo qualitative improvements. Genetic modification, breeding and selection are some crop improvement techniques that are not successful at the moment in developing varieties that can replace current world varieties. Somaclonal variation is another technique for obtaining desirable variants, which have been achieved in crops such as sugarcane, wheat and sorghum. Highly stable variants that can be transmitted to progenies, and a more controlled change of their characteristics than those of induced mutations were achieved. However, this technique requires a plant regeneration system from callus cells. These cells have a tendency to mutate, and more cells are mutated under prolonged culture and rapid proliferation, and so generate more variants for selection. Therefore, the objectives of this project are to induce calli, proliferate old calli and regenerate shoot from calli. For calli induction, meristemic globular bodies (MGB) of Moris and Josapine, were cultured in various levels of auxin naphthaleneacetic acid (NAA) and 2,4-dichlorophenoxyacetic (2,4- D). The highest percentage of MGB forming calli was observed in treatment NAA 14 and 10 mg/L for Moris and Josapine respectively, at the end of 16 weeks. For calli proliferation, 18 month-old calli were cultured in various levels of NAA, 2,4-D, bnaphtoxyacetic acid (BNOA) and p-chlorophenoxyacetic acid (4-CPA) auxins for 12 weeks, and then in various levels of casein hydrolysate (CH) and coconut water (CW) in the presence of NAA 6 mg/L for 12 weeks. Among the various levels of the four auxins, NAA 6 mg/L proliferated healthy and high mean calli fresh weight. However, NAA 6mg/l supplemented with CW and CH also gave healthy and generally higher mean calli fresh weight than NAA 6mg/L alone. NAA 6 mg/L alone was considered the most economical treatment for calli proliferation, while NAA 6mg/L supplemented with 15%v/v CW and 300mg/L CH gave significantly highest mean calli fresh weight and was considered the best treatment for rapid calli proliferation. For shoot regeneration, 18 month-old calli were cultured in various levels of NAA, 2,4-D, BNOA and 4-CPA auxins for 12 weeks, and then in combinations of various levels of auxins (BNOA and 2,4-D) and cytokinins (Benzylaminopurine [BAP], Kinetin and Adenine) for 12 weeks. Among the various levels of the four auxins, 2,4-D at 1mg/L regenerated high number of shoots, and was considered the best treatment for high shoot regeneration from calli that were considered as high competency calli. However, regeneration response from these calli were gradually decreasing, such that treatment BNOA 6mg/L combined with BAP 1mg/L (with subculture) (that statistically gave highest number of regenerated shoots) and an extended culture period of 12 weeks (without subculture), generated mean number of shoots was considered as not satisfactory. Subsequently, the 18 month old-calli (now 27 months) were cultured in various combination levels of CH and CW for 12 weeks, but these failed to show any regenerated shoots from calli that were now considered low competency calli. However, calli obtained from treatment NAA 6 mg/L + 300mg/l CH + 15%v/v CW (rapid calli proliferation treatment, and now 27 months old), preserved calli competency and regenerated highest mean number of shoots in treatment 10%v/v CW and 200mg/l CH, and was considered the best treatment for regeneration of shoots from low competency calli.